THE ROLE OF MULTIPLE STAKEHOLDERS IN THE IMPLEMENTATION OF FOOD POLICY THROUGH GOVERNMENT PARTNERSHIPS WITH AGRICULTURAL START-UPS (CASE STUDY IN MADIUN REGENCY) (International Journal of Cultural and Social Science, 2026)
This study examines the implementation of food policy through a partnership between the Madiun Regency Government and PT Eratani Teknologi Nusantara to strengthen food security and improve farmers’ welfare. The study employs a qualitative approach using a case study method, conducted in Balerejo Sub-district, Madiun Regency. Data collection was carried out through interviews, observations, and documentation involving government agencies, agricultural extension officers, Bulog, PT Eratani Teknologi Nusantara, and farmers. The results of the study indicate that multi-stakeholder collaboration makes a significant contribution to the effectiveness of food policy implementation through increased agricultural productivity, expanded access to finance, the utilisation of digital technology, and improved market access for farmers. Rice productivity increased from 6.2 tonnes/ha to 7.8 tonnes/ha following the implementation of the partnership programme. Furthermore, farmers experienced increased income and a stronger bargaining position within the agricultural supply chain. This study also identified several implementation challenges, including limited integration of agricultural data, low technological literacy among farmers, and weak farmer succession. This study underscores the importance of sustainable agritech-based partnerships in strengthening regional food security through collaborative governance, technological innovation, and inclusive farmer empowerment.